Online placement for dynamically reconfigurable devices. (6th June 2006) - Ahmadinia, Ali; Bobda, Christophe; Teich, Jurgen
Reconfigurable hardware components such as FPGAs are used more and more in embedded systems, since such components offer a sufficient capacity for a complete SoC(System on a Chip) or even NoC(Network on a Chip). In order to use efficiently the dynamic and partial reconfiguration possibility on such components, one needs a support in the form of operating systems to manage both software and reconfigurable hardware. Online placement is one of these management issues that is investigated in this paper. Here we present a new approach for online placement of modules on reconfigurable devices. Also an optimisation of communication between running modules themselves and outside of the chip is proposed. The experimental results show a considerable decrease in communication and routing costs. Also task scheduling between hardware and software is investigated and a communication infrastructure for online placement has been proposed and implemented.